When proof meets personality: A study of artisan-type prospective teachers in mathematical problem-solving - Widyastuti, Rany; Dimas Danar Septiadi; Ikha Yuliati; Fitriyatul Qomariyah; Fatimatuz Zahroh (Universitas Islam Negeri Raden Intan Lampung, 2025)
Mathematical problem-solving ability is an essential skill for prospective teachers; however, many students still face difficulties, particularly in proof-based problems. Previous studies have mostly examined personality types in the context of application-based tasks, so there has been limited attention to students’ mathematical problem-solving abilities with the artisan personality type in dealing with proofs of statements. UIN Madura students in the Mathematics Education study program tend to have an artisan personality. They have a tendency to solve problems by using a common pattern. Therefore, when they faced mathematical proof comprehension problems, they often experienced difficulties and limitations. This made the researcher interested in conducting a study that aims to describe the abilities of UIN Madura students in the Mathematics Education study program in solving mathematical problems based on Polya's theory viewed from the artisan personality type. This study is a descriptive qualitative study. The subjects of this study were two students with the artisan personality type. Data collection instruments used questionnaires (personality type data), essay tests (problem-solving abilities), and interviews. Data analysis techniques used the Miles and Huberman technique. Based on the research results, it is known that artisan-type students can understand problems, make plans, and solve problems correctly but cannot re-check the results they have obtained. This indicates the tendency of artisan-type students to choose quick and simple approaches, yet with less accuracy in the verification process. This study contributes to the scientific development by highlighting the distinctive characteristics of artisan-type students in solving mathematical proofs. The findings of this research can serve as a basis for educators in designing learning strategies that are more aligned with students’ personalities.